Evaluate
lim x → 0 sin x e x − e − x
If the limit does not exist. Type in "99999"
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Or you can solve it simply using some fundamental limits and a little manipulation.
x → 0 lim ( sin x e x − e − x ) = x → 0 lim ⎝ ⎜ ⎛ x sin x x e x − 1 − ( e − x + 1 ) ⎠ ⎟ ⎞ = x → 0 lim ⎝ ⎜ ⎜ ⎛ 1 x → 0 lim ( x e x − 1 ) + − x → 0 lim ( − x e − x + 1 ) ⎠ ⎟ ⎟ ⎞ = 1 + 1 = 2
You can also see the solution by visualizing that sinh ( x ) = 2 e x − e − x so x → 0 lim sin ( x ) e x − e − x = 2 x → 0 lim sin ( x ) sinh ( x ) = 2 x → 0 lim x sinh ( x ) sin ( x ) x = 2
by the fundamental trigonometric limit x sin ( x ) and x sinh ( x ) when x → 0 iquals 1.
I did it exactly by the same way c:
Problem Loading...
Note Loading...
Set Loading...
Because this is an indeterminant form zero over zero, we can use L'Hopital's rule. We evaluate this limit by taking the derivatives of the top and the bottom.
lim x → 0 d x d ( sin x ) d x d ( e x − e − x ) = lim x → 0 cos x e x − ( − e − x ) = lim x → 0 cos x e x + e − x
This simplifies to 2